The latest research on risk factors and pathomechanisms of depression - review - Magdalena Kozyra; Martyna Nowińska; Jakub Klas; Michalina Pytka; Urszula Łopuszańska (Kazimierz Wielki University, 2020)
Introduction: Depression is a mental disorder that is increasingly being diagnosed in middle and more developed countries (MDC). Symptoms of depression in patients with severe depressive disorder (MDD) include sadness, regret, negative thoughts, anxiety, and more. The aim of the study: The aim of the study was to summarize the latest research (from 2020) on factors related to the occurrence of depression, as well as the current findings on depression (also those related to the COVID-19 pandemic). Material and method: For this purpose, scientific search engines such as PubMed and Google Scholar were used. Description of the state of knowledge: In 2020, apart from research on pathomechanisms and environmental factors, a large part of the research focused on the COVID-19 pandemic as a risk factor for the development of depression symptoms. Many studies from different parts of the world have confirmed that a pandemic can have a significant impact on the occurrence of depression. Summary: There are many factors that can cause depression and it is important to keep them in mind both in everyday life and in clinical practice. Studies from various parts of the world have shown that the COVID-19 pandemic has exacerbated the experience of depressive symptoms, also in those who have not yet been diagnosed with MDD. The degree of severity of depressive symptoms depended on such factors as: financial situation, social isolation.